Effect Of Exposure to the traumatic event location in war veterans with Post Traumatic Stress Disorder - M.R. khodaie ardakani; M.S. khanjani; A. mirabzadeh; B. bahmani; E. abtahi; G. Sadighi; J. mirzaii (Afarand Scholarly Publishing Institute, 2014)
Background& Purpose: The Purpose of this study was to evaluate the effect of specific type of exposure, visiting the stressful event location, on PTSD symptoms are caused by the war. Methods & Material: This is an intervention study and data are measured as before and after. Twenty five people with PTSD symptoms were selected based on inclusion criteria. The intervention was exposure to traumatic event place that caused PTSD, For this purpose each of these people were sent to combat zones. PTSD check list (PCL) before exposure, 2 weeks and 3 months after that, was completed by the participants and then Paired t- test was used to compare of 3 measurements as before, after and follow-up 3 months after exposure and analysed with SPSS /16 software. Results: The effect of this exposure on overall symptoms of PTSD was significant (p<0.05) and difference in mean scores between before,2 weeks , also 3 minutes after exposure was respectively -3.45 and -4.41. Difference between mean scores of the subscales Re experience and Hyper arousal in before, 2 weeks , 3 months after exposure was significant(p<0.05). But, Difference of mean scores in avoidance/numbness symptoms was not significant (p>0.05). Conclusion: Exposure to the traumatic event place decreased the overall symptoms of PTSD and also Re experience and Hyper arousal symptoms.